Wasting Stunting (WaSt) Among Toddlers 6-23 Months in Indonesia - Hanik Anur Maria; Azam, Widya Hary Cahyati; Azam, Intan Zainafree; Azam, Ferry Santoso; Azam, Safira Chairani Dimarti (Public Health Perspective Journal, 2025)
Wasting stunting (WaSt) is a condition in which wasting and stunting occur in a child at the same time. In Indonesia, the prevalence of WaSt was 2.4% among children 6 to 59 months in 2021 (Jokhu & Syauqy, 2024).  Research on factors related to WaSt has not been widely conducted in Indonesia. The purpose of this study is to find out the factors associated with WaSt among toddlers aged 6–23 months in Indonesia. This study is analytical research with a cross sectional design using SSGI 2022 data. The population in this study is all toddlers among SSGI 2022 respondents. The sample in this study is toddlers aged 6–23 months in Indonesia. The sampling technique used was the total sample. The sample in this study was 41257 toddlers (6–23 months). The prevalence of stunting, wasting, underweight, and WaSt was 16.1%, 7.62%, 11.8%, and 1.15%, respectively. Variables related to the incidence of wasting stunting (WaSt) were diarrhea (PR = 1,331), pneumonia (PR = 2,599), pulmonary tuberculosis (PR = 4,048), birth weight (PR = 4,571), birth length (PR = 2,437), mothers' education level (PR = 1,213), and mothers' work (PR = 1,525). Factors related to WaSt among toddlers aged 6–23 months in Indonesia are diarrhea, pneumonia, pulmonary TB, birth weight, birth body length, maternal education level, and maternal employment.